2000
DOI: 10.1200/jco.2000.18.14.2676
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Study Comparing Conventional-Dose Doxorubicin Plus Ifosfamide Versus High-Dose Doxorubicin Plus Ifosfamide Plus Recombinant Human Granulocyte-Macrophage Colony-Stimulating Factor in Advanced Soft Tissue Sarcomas: A Trial of the European Organization for Research and Treatment of Cancer/Soft Tissue and Bone Sarcoma Group

Abstract: The use of rhGM-CSF allowed safe escalation of chemotherapy doses. Despite a 50% increase of the doxorubicin dose-intensity, the high-dose regimen failed to demonstrate any impact on survival in patients with ASTS. The low complete response rate, the high incidence of leiomyosarcomas, and liver metastases may in part explain these results. However, the lengthening of the PFS in the intensive arm, because of the quality of stable disease and inappropriate tumor evaluation policies that potentially lead to an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
149
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(156 citation statements)
references
References 30 publications
3
149
1
3
Order By: Relevance
“…Although this observed response rate did not reach the requirement being considered promising as defined by the statistical design, it is in the range of similar response rates (40 -66%) for high-dose combination of ifosfamide and doxorubicin that have been obtained in other phase-II studies (Frustaci et al, 1997;Patel et al, 1998;Reichardt et al, 1998). The most recent trials have yielded less impressive response rates (25 -23%) but were designed such that only one agent was administered at high dose levels (Le Cesne et al, 2000;Worden et al, 2005). Indeed, the efficacy of ifosfamide alone at standard dose (5 g m À2 ) was shown to be minimal (10%) in a randomised trial (van Oosterom et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this observed response rate did not reach the requirement being considered promising as defined by the statistical design, it is in the range of similar response rates (40 -66%) for high-dose combination of ifosfamide and doxorubicin that have been obtained in other phase-II studies (Frustaci et al, 1997;Patel et al, 1998;Reichardt et al, 1998). The most recent trials have yielded less impressive response rates (25 -23%) but were designed such that only one agent was administered at high dose levels (Le Cesne et al, 2000;Worden et al, 2005). Indeed, the efficacy of ifosfamide alone at standard dose (5 g m À2 ) was shown to be minimal (10%) in a randomised trial (van Oosterom et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Lower-dose combinations led to severe neutropenia in 87 -90% and severe infection in 17% of patients (Le Cesne et al, 2000;Worden et al, 2005). One of these studies involved two toxic deaths out of 40 patients, severe thrombopenia in 50 -62% and severe anaemia in approximately 50% of patients (Worden et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demonstration of a benefit in other larger randomized trials in improving progression-free survival suggests that the use of chemotherapy for this reason still may be valid. 14 It remains unclear which chemotherapy regimen is superior: One large randomized trial suggested that the addition of ifosfamide added little benefit over single-agent doxorubicin in increasing progression-free survival. 15 It is possible that there may be other benefits to chemotherapy that were not documented in this study, such as palliation of symptoms or shrinkage of the tumor, that may facilitate less extensive surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Schemes with anthracyclines and ifosfamide at adequate doses are those most widely used as first line treatments, especially where a greater shrinkage of lesions may lead to an improvement in long-term results (1, 2). Yet the most optimistic expectancy of the above combination with respect to response rate is less than 30%, and as regards progression-free survival, it is less than 8 months, according to phase III trials in advanced disease (3). These results have barely been improved upon in the last 2 decades, in spite of some evidence of dose-response relationship for both drugs (4).…”
Section: Introductionmentioning
confidence: 88%